Are Inconclusive Decisions in Forensic Science as Deficient as They Are Said to Be? - Biedermann, Alex; Bozza, Silvia; Taroni, Franco; Vuille, Joëlle (Frontiers in Psychology, 2019)
Many quarters of forensic science use reporting formats such as ‘identification’, ‘inconclusive’ and ‘exclusion’. These types of conclusions express opinions as to whether or not a particular person or object is the source of the material or traces of unknown source that is of interest in a given case. Rendering an ‘inconclusive’ conclusion is sometimes criticised as being inadequate because – supposedly – it does not provide recipients of expert information with helpful directions. In this paper, we critically examine this claim using decision theory. We present and defend the viewpoint according to which deciding to render an ‘inconclusive’ conclusion is, on a formal account, not as inadequate as may commonly be thought. Using elements of decision theory from existing accounts on the topic, we show that inconclusive conclusions can actually be viable alternatives with respect to other types of conclusions, such as ‘identification’.